NATURE AND MAGNITUDE OF GENE ACTION AND GENETIC COMPONENTS OF VARIATION FOR YIELD AND YIELD CONTRIBUTING CHARACTERS IN F2 GENERATION OF SESAME (SESAMUM INDICUM L.) - D. M. VEKARIA; K. L. DOBARIYA; C. J. RAJANI; M. B. PATEL (The Bioscan, 2015)
The results on 6x6 F2 diallel in sesame revealed that additive component (D) was significant for days to 50 % flowering (4.11± 0.51), days to maturity (7.18± 1.26), plant height (114.57 ± 6.58), height to first capsule (31.80 ± 2.651), number of branches per plant (0.31± 0.033), number of internodes per plant (4.15 ± 0.48), number of capsules per plant (43.72 ± 9.74), number of capsules per leaf axil (0.32 ± 0.010) and oil content (1.85 ± 0.17). The genetic variances of dominant components (H1 and H2) were significant for majority of characters. An equal distribution of increaser and decreaser genes in the parents was found for all the characters except for plant height, height to first capsule, number of internodes per plant and number of capsules per leaf axil. Narrow sense heritability was high for height to first capsule (0.72), plant height (0.66), number of branches per plant (0.67), length of capsule (0.64) and number of seeds per capsule (0.54). Biparental mating or diallel selective mating has been suggested for further genetic improvement.